Argo Parahyangan Train Service Quality Improvement (The Indonesian Journal of Business Administration, 2012)
Argo Parahyangan train passenger volume declined since the opening of Highway Cipularang. This is due to the emergence of competing business that is passenger transport transportation travel point to point as well as inter-city buses. Due to continued losses, PT Kereta Api Indonesia combines two previously with Bandung-Jakarta route the Argo Gede and Parahyangan. It is intended to further save on maintenance costs and increases revenue. However, passenger trains continued to decrease in volume as the growth of business travel point to point.To find out what the cause of the increase in passenger volume reduction, is necessary to find the root cause of the problem first. Needs to be analyzed from all sides as the analysis of the company's external and internal analysis of the company. External analysis conducted by analyzing Framework PESTEL and Porter's Five Forces. Internal analysis conducted by analyzing corporate strategy, business strategy, Segmenting Targeting Positioning (STP), and the marketing mix (7P) PT Kereta Api Indonesia. Then do the retrieval questionnaires to passengers for the analysis of the quality of products, tariffs, and services using the Importance-Performance Analysis (IPA). Finding from this research in PT KAI is not the focus in the development of management because too many train set, education officials are still low, investments in railway development is still lacking, the promotion of a less. Objective of this research is to provide the proposed service quality implementation PT Kereta Api Indonesia and implementation of plans and programs to enhance customer satisfaction. With the suggestions given Argo Parahyangan passenger volume expected to be up front and get a high profit Keywords: PT Indonesian Railways, passenger volume, Importance-Performance Analysis (IPA)